2023
DOI: 10.1108/ijchm-07-2022-0913
|View full text |Cite
|
Sign up to set email alerts
|

Text classification in tourism and hospitality – a deep learning perspective

Abstract: Purpose This study aims to investigate the current state of research using deep learning methods for text classification in the tourism and hospitality field and to propose specific guidelines for future research. Design/methodology/approach This study undertakes a qualitative and critical review of studies that use deep learning methods for text classification in research fields of tourism and hospitality and computer science. The data was collected from the Web of Science database and included studies publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…Moreover, this study found that sophisticated neural networks and deep learning algorithms, such as convolution neural networks (CNNs) and long short-term memory (LSTM) models, were on the rise in AI methods research during the study period. These advanced neural network algorithms were used mostly for classification and prediction, given their ability to handle complex data and their high accuracy (Liu et al , 2023). In line with Doborjeh et al (2022), this study found that these advanced AI-based models were most frequently adopted in research on demand forecasting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this study found that sophisticated neural networks and deep learning algorithms, such as convolution neural networks (CNNs) and long short-term memory (LSTM) models, were on the rise in AI methods research during the study period. These advanced neural network algorithms were used mostly for classification and prediction, given their ability to handle complex data and their high accuracy (Liu et al , 2023). In line with Doborjeh et al (2022), this study found that these advanced AI-based models were most frequently adopted in research on demand forecasting.…”
Section: Resultsmentioning
confidence: 99%
“…First, AIGCs, such as AI-generated editorials, graphics and videos, could be a new type of data source in AI methods research. Second, hospitality researchers could leverage the co-pilot of generative AI applications to augment their coding skills in data collection and analysis (Liu et al , 2023). Albeit with assistance of these tools, researchers still need to improve their capability in searching for valuable research questions, selecting appropriate research method and algorithms and properly applying and communicating this knowledge in their research to publish in top hospitality journals.…”
Section: Methodsmentioning
confidence: 99%
“…The DL technique must be applied to extract significant information on various features that affect review helpfulness. The hospitality and tourism industries have widely applied the DL technique, which offers numerous advantages (Essien and Chukwukelu, 2022; Liu et al , 2023). First, unlike the traditional ML approach, the DL technique is a data-driven approach that does not rely on assumptions regarding the data.…”
Section: Literature Review and Research Backgroundmentioning
confidence: 99%
“…Berdasarkan studi literatur yang dilakukan [23], secara umum teknik machine learning yang banyak digunakan pada penelitian analisis sentimen atau opinion mining adalah Naïve Bayes (NB), support vector machine (SVM), dan neural network (NN) karena memiliki performa yang baik. Di samping itu, algoritma Deep Learning (DL) sebagai variasi bentuk neural network dengan lapisan yang lebih banyak turut mengalami peningkatan popularitas penggunaan pada penelitian analisis sentimen [23], [24]. Penelitian yang dilakukan [25] menggunakan algoritma NB, SVM dan Random Forest (RF) untuk klasifikasi sentimen review destinasi wisata menyimpulkan algoritma SVM memiliki tingkat akurasi lebih baik yaitu 67,97% dibandingkan algoritma NB (61,33%) dan RF (63,55%).…”
Section: Pendahuluanunclassified